Organizational politics and work-family conflict: the hospitality industry in Bangladesh. (3rd July 2020) - Arefin, Md. Shamsul; Alam, Md. Shariful; Islam, Nazrul; Molasy, Mateusz
Abstract : Purpose: Researchers have shown increasing interest, in recent times, in organizational politics and how it affects employees and organizations. This paper aims to investigate how perceived organizational politics (POPS) impact employee behaviors such as task performance, organizational citizenship and turnover intention, by affecting work-family conflict. Design/methodology/approach: A sample of 287 full-time frontline hotel employees in Bangladesh was collected. A hierarchical regression analysis was applied to test the hypotheses. Data were analyzed using SPSS and AMOS software. Findings: The results show that work–family conflict plays a mediating role in the indirect effect of POPS on task performance, organizational citizenship behavior (OCB) and turnover intention. The findings of the study also suggest that POPS has a positive association with work–family conflict and turnover intention, and negative association with task performance and OCB. Research limitations/implications: This study cannot confirm causal inference, which can be the scope for future studies. Practical implications: Managers may design the work environment in ways that ensure work and family interface and employee retention. Training programs can help employees deal with organizational politics and potential impact on work and nonwork problems. Managers should provide employees with the necessary support to sustain in-role and extra-role behavior in the political environment. Originality/value: To the best of our knowledge, no prior studies have been carried out with this scope in the South Asian context.